Receptor activator of nuclear factor-κB ligand-mediated osteoclastogenesis signaling pathway and related therapeutic natural compounds - Qu, Zechao; Zhang, Bo; Kong, Lingbo; Gong, Yining; Feng, Mingzhe; Gao, Xiangcheng; Wang, Dong; Yan, Liang (Frontiers in Pharmacology, 2022)
Osteoclast is a hematopoietic precursor cell derived from the mononuclear macrophage cell line, which is the only cell with bone resorption function. Its abnormal activation can cause serious osteolysis related diseases such as rheumatoid arthritis, Paget's disease and osteoporosis. In recent years, the adverse effects caused by anabolic anti-osteolytic drugs have increased the interest of researchers in the potential therapeutic and preventive effects of natural plant derivatives and natural compounds against osteolytic diseases caused by osteoclasts. Natural plant derivatives and natural compounds have become major research hotspots for the treatment of osteolysis-related diseases due to their good safety profile and ability to improve bone. This paper provides an overview of recent advances in the molecular mechanisms of RANKL and downstream signaling pathways in osteoclast differentiation, and briefly outlines potential natural compounds with antiosteoclast activity and molecular mechanisms.